Management of vampire bats and rabies: a precaution for rewilding projects in the Neotropics - Gonçalves, Fernando [UNESP]; Galetti, Mauro; Streicker, Daniel G. (My University, 2021)
Changes in animal population dynamics and community composition following species (re)introduction may have unanticipated consequences for a variety of downstream ecosystem processes, including infectious disease transmission. Due the lessons learned from ongoing projects, we present a novel approach on how to anticipate, monitor, and mitigate the vampire bats and rabies in rewilding projects. We pinpoint a series of precautions and the need for long-term monitoring of vampire bats and rabies responses to rewilding projects and highlighted the importance of multidisciplinary teams of scientist and managers focusing on prevention educational program of rabies risk transmitted by bats. In addition, monitoring the relative abundance of vampire bats, considering reproductive control by sterilization and oral vaccines that autonomously transfer among bats would reduce the probability, size and duration of rabies outbreaks. The rewilding assessment framework presented here responds to calls to better integrate the science and practice of rewilding and will help conservation practitioners and researchers to develop effective message framing strategies that minimize bats emerging infectious diseases and support biodiversity and its associated ecosystem services.
Keywords: Animal restoration; Bat-transmitted pathogen; Human and animal mortality; Multidisciplinary teams; Oral vaccines; Reproductive control